Pemanfaatan Penggunaan Aplikasi Web Notion Untuk Mengelola Manajemen Pada JPRMI - Budi, Eko Setia; Zuraidah, Eva; Sugiyarto, Ipin; Sulthon, Besus Maula; Perwitasari, Ayu; Anggata, Aprio Riska; Agustina, Menik Anna; Krishandi, Septa Remond; Nursalim, Fredrika Irmanielyn (Journal of Social Responsibility Projects by Higher Education Forum, 2024)
In this community service, the aim is to explore the role of the Notion application in increasing productivity. Notion is an all-in-one workspace application used for taking notes, managing knowledge and data, and managing projects and tasks. Initially, this application was intended to create notes or notes with a simple appearance of Karang Taruna in managing the system. Karang Taruna is a social organization as a forum and means of developing every member of society that grows and develops on the basis of social awareness and responsibility from and for the community, especially the younger generation in the region, especially engaged in social welfare efforts. While the membership of the DKI Jakarta Mosque Youth and Teenagers Network (JPRMI), hereinafter referred to as the DKI Jakarta Mosque Youth and Teenagers Network (JPRMI) is every member of society. Limited understanding of the management of information system management that has not been carried out in optimization in the JPRMI management environment. The system management used is still manual for the JPRMI DKI Jakarta membership information system. Therefore, Nusa Mandiri University is carrying out Community Service in the form of Utilizing the Use of the Notion Web Application to Manage Management at PRMI DKI Jakarta. With this training, it can help the DKI Jakarta Mosque Youth and Teenagers (JPRMI)